Prevention, diagnosis and treatment of venous thromboembolism - Dominik Machaj; Katarzyna Cyboran; Alicja Płaczek; Marlena Baran; Michał Wojnowski (Kazimierz Wielki University, 2020)
The formation of a thrombus in a vein leads to a narrowing of its lumen and a reduction in blood flow, which results in the development of venous thromboembolism (VTE). It manifests itself in most cases, including pain, swelling and redness of the affected limb. Data published in 2007 indicate that in 6 European Union countries as many as 370,000 deaths per year are a consequence of deep vein thrombosis (DVT), which is 75% a consequence of hospitalization. [2] [11] The causes of blood clots are found in the factors of the so-called Virchow triad. The main risk factors for venous thromboembolism as well as its complications of pulmonary embolism include thrombophilia, advanced age, previous VTE, immobilization of trauma or surgery. In the diagnosis of VTE, the determination of D-dimer level plays a key role.